Aqueous zinc–sodium hybrid battery based on high crystallinity sodium–iron hexacyanoferrate. (June 2021) - Yuan, X.; Ma, F.; Chen, X.; Sun, R.; Chen, Y.; Fu, L.; Zhu, Y.; Liu, L.; Yu, F.; Wang, J.; Wu, Y.
Abstract: Owing to their advantages of non-toxicity, non-flammability, and ultrahigh ionic conductivity, aqueous rechargeable batteries are regarded as promising candidates for energy storage systems (ESSs). Currently, electrode materials are key factors in determining the performance of aqueous batteries. In this study, a high crystallinity sodium–iron hexacyanoferrate (Na–FeHCF) with low vacancy and low water content was successfully synthesized. It can promote the rapid transfer of Na + and maintain the structural stability during the repeated insertion/extraction cycles of Na + . Owing to these features, it presents better electrochemical performance than the ordinary one. Overall, the assembled aqueous zinc–sodium hybrid battery displays excellent electrochemical performance with an energy density of 132.5 Wh kg −1 and cycling stability of 77.5% capacity retention after 800 cycles. These results show great promise for the aqueous hybrid batteries in application for ESSs. Graphical abstract: Aqueous zinc–sodium hybrid battery was assembled using Prussian blue with high crystallinity, low vacancy, and low water content as positive electrode shows excellent rate performance, stable cycle performance, and delivers a high energy density of up to 132.5 Wh kg −1 . Image 1 Highlights: Aqueous rechargeable batteries are promising safe energy storage systems. An aqueous zinc–sodium hybrid battery with excellent electrochemical performance is reported. Its positive electrode is a high crystallinity sodium–iron hexacyanoferrate. Its energy density can be 132.5 Wh kg −1 with good cycling stability.